Find the product mentally. (r - s)2 2r2 - rs - s2 r2 - 2rs s2 r2 - rs s2

Question

Asked 3/15/2016 7:23:32 AM

Updated 3/16/2016 5:22:13 AM

2 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by jeifunk [3/16/2016 5:22:10 AM]

s

=r^2 - rs - rs + s^2

=r^2 - 2rs + s^2

Stick222|Points 0|

= (2m - 9)(2m - 9)

= 4m^2 - 36m + 81

=(ab + 3)(ab + 3)

=(ab)(ab) + (ab)(3) + (3)(ab) + (3)(3)

=a^2b^2 + 3ab + 3ab + 9

=a^2b^2 + 6ab + 9

jeifunk|Points 66996|

Question

Asked 3/15/2016 7:23:32 AM

Updated 3/16/2016 5:22:13 AM

2 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by jeifunk [3/16/2016 5:22:10 AM]

Rating

8

(n + 7)^2

= (n + 7)(n + 7)

= n^2 + 7n + 7n + 49

= n^2 + 14n + 49

= (n + 7)(n + 7)

= n^2 + 7n + 7n + 49

= n^2 + 14n + 49

Added 3/16/2016 5:10:31 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/16/2016 5:22:18 AM]

Multiply (6z 2 - 4z + 1)(8 - 3z). **Weegy:** (6z^2 - 4z + 1)(8 - 3z) = -18z^3 + 12z^2 - 3z + 48z^2 - 32z + 8 = -18z^3 + 60z^2 - 35z + 8 **User:** Simplify b(a + b) - a(a - b). **Weegy:** b(a + b) - a(a - b) (ab + b^2) - (a^2 + ab) = -a^2 +2ab + b^2 **User:** Find the product.
(2p + 7)(3p - 9) **Weegy:** (2p + 7)(3p - 9) = 6p^2 - 18p + 21p - 63 = 6p^2 + 3p - 63 **User:** Find the product.
-2x(x 2 - 3) **User:** Find the quotient.
(35n 3 - 30n 2 + 25n) ÷ (-5n) **Weegy:** (35n^3 - 30n^2 + 25n) / (-5n) = -7n^2 + 6n - 5 **User:** Find the product.
3y 2 z(2y 2 z + 4yz - y + z) **Weegy:** 3y^2z(2y^2z + 4yz - y + z) = 3y^2z*2y^2z + 3y^2z*4yz - 3y^2z*y + 3y^2z*z = 6y^4z^2 + 12y^3z^2 - 3y^3z + 3y^2z^2 **User:** Find the product.
(6a + b)2 **Weegy:** (6a + b)^2 = 36a^2 + 6ab + 6ab + b^2 = 36a^2 + 12ab + b^2 **User:** Find the product.
(7q - 5)(7q + 5) **Weegy:** (7q - 5)(7q + 5) = 49q^2 + 35q - 35q - 25 = 49q^2 - 25 **User:** Find the quotient.
y 9 ÷ y 3 (More)

Question

Updated 3/16/2016 5:45:38 AM

2 Answers/Comments

-2x(x^2 - 3)

= -2x*x^2 + (-2x)*(-3)

= -2x^3 + 6x

= -2x*x^2 + (-2x)*(-3)

= -2x^3 + 6x

Added 3/15/2016 6:26:54 PM

This answer has been confirmed as correct and helpful.

Factor 16p 4 - 24p 3. **Weegy:** 16p^4 - 24p^3 = 8p^3(2p - 3) **User:** Factor 4n 4 + n 3. **Weegy:** 4n^4 + n^3 = n^3(4n + 1) **User:** Factor 14a - 7b. **Weegy:** 14a - 7b = 7(2a - b) (More)

Question

Updated 3/15/2016 10:12:07 AM

0 Answers/Comments

32,539,392

questions answered

There are no comments.